P16 Endoloop ligatures in the retrieval of urethral foreign bodies: a narrative review. (22nd July 2022) - Narroway, H; Parkin, C; Latif, E
Abstract: Introduction: Self-insertion of foreign bodies into the urethra has been described previously in patients presenting to hospital emergency services. Treatment typically involves procedural retrieval under local anaesthesia using basket or forceps, cystoscopy, or open surgery. An Endoloop is a device designed to snare colonic polyps during endoscopy with nylon loops. It is not traditionally used for retrieval of urethral foreign bodies. Our objective was to determine the incidence, safety and efficacy of this approach. Methods: A narrative review was performed. Primary outcomes were technical success, defined as uncomplicated retrieval of foreign body, and adverse events related to pain, bleeding, infection, and damage to structures. Electronic searches were performed using PubMed, Embase and Google Scholar. Reference lists of selected studies were searched manually. Results: 2 case studies met inclusion criteria for analysis, both describing self-insertion of urethral foreign bodies for purposes of sexual arousal. These comprised a 30-year-old male (magnets) and a 29- year-old female (metal urethral sound). Both patients underwent successful retrieval of foreign body using an Endoloop ligature. There were no symptoms post-operatively and no procedural complications were reported. Conclusion: An Endoloop ligature should be considered in conjunction with endoscopy when difficulties are experienced or anticipated with basket or forceps retrieval. Follow-up is mandatory to monitor for complications due to foreign body insertion such as urethritis, incontinence, fistula and diverticulum formation. Referral to psychological services is encouraged to reduce the risk of recurrence. Further studies are required to validate the efficacy and safety of this technique. Take-home message: An Endoloop ligature should be considered in conjunction with endoscopy when difficulties are experienced or anticipated with basket or forceps retrieval of urethral foreign bodies.